THE INFLUENCE OF SERVICE QUALITY ON CONSUMER SATISFACTION (STUDY ON RESTAURANTS AND RESTAURANTS IN KARO DISTRICT - Lubis, Sri Rosliana (Akademi Pariwisata Darma Agung, 2022)
This study aims to analyze the effect of service quality (physical evidence, reliability, responsiveness, assurance and empathy) on customer satisfaction at restaurants and restaurants in Karo Regency. The analytical method used in this research is descriptive statistical analysis and linear regression analysis. The results showed that physical evidence (X1) had a positive and significant effect on customer satisfaction. Reliability (X2) has a positive and significant effect on customer satisfaction. responsiveness (X3) has no significant effect on customer satisfaction. Assurance (X4) has a positive and significant effect on customer satisfaction. and Empathy (X5) has no significant effect on customer satisfaction.